Effect of Full Annealing and Single Quenching-Tempering Heat Treatment on the Mechanical Properties of JIS SUP 9A Steel - Andreas Luki Indratmoko; Irza Sukmana; Mohammad Badaruddin (Jurnal POLIMESIN, 2023)
JIS SUP 9A leaf spring steel under hot-forging conditions was subjected to full annealing (FA) and single step-quenching-tempering heat treatments (SQT). Tensile test specimens to ASTM E 8 standards have been prepared. The FA process was performed by heating all specimens in the furnace at a constant temperature of 800°C for 2 hours, followed by cooling in the furnace. Then, all test specimens were heat-treated SQT. The SQT process was carried out by heating all samples in a furnace at 800°C for 1 hour and 650°C for 1 hour, each followed by immersion in crude palm oil (CPO) media at a liquid temperature of 70°C until the specimens reached 100°C. The FA process removes internal stresses with high microstructural softness and SQT produces a fine martensitic phase microstructure, which improves mechanical strength (tensile strength and impact strength) with good ductility. Electron and scanning microscopy have been used to determine the concentration of impurities and microstructural changes in relation to the mechanical properties of the specimen concerned. The results showed that the yield limit, maximum tensile stress, and impact energy increased by 113.5%, 16.3%, and 705.2%, respectively. However, hardness decreased by 18.8% for SQT specimens against FA after heat treatment. This research utilizes industrial waste, which is available quite a lot; in the future, it will become an alternative for handling environmental problems. The abundant availability of raw materials and resulting strength-toughness are the main advantages of this heat treatment